Staffing Is More Than a Number: Using Workflow to Determine an Appropriate Nurse Staffing Ratio in a Tertiary Care Neurocritical Care Unit. Issue 5 (October 2018) - Hill, Michelle; DeWitt, Jessica
Abstract : ABSTRACT: Objective: To enhance nursing staff retention and ensure a consistently high standard of care, a study was conducted to determine an appropriate nurse staffing model for a neurocritical care unit. In addition to being critically ill, these patients often require extensive diagnostic testing to determine treatment. Nurses traveling with patients leave higher nurse-patient ratios remaining on the unit.Methods: Prospective observation was used to assess relationships between neurologic assessment, documentation, and the amount of time spent traveling with patients. Patient acuity and nursing experience were also measured.Results: Over the 30-day study period, more than 226 hours were spent traveling, equivalent to approximately 38% of a single nurse's shift. There was no correlation between the experience of nurses and the time necessary to perform a neurologic assessment. When controlling for acuity, a relationship was found between nursing experience and the time needed to chart an assessment.Conclusions: Significant time was spent every day off the floor, in addition to the documentation and performance of frequent assessments. These results advocate for a staffing position without a dedicated patient assignment but to assist with traveling and high-acuity patients so that safe and attentive care can be consistently given. Abstract : Supplemental digital content is available in the text.